The flag the story of Revd David Railton MC and the tomb of the unknown warrior - Richards, Andrew (Casemate Publishers, 2017)
"Reverend David Railton MC served as a chaplain on the Western Front during World War I. Attached to three divisions between 1916 and 1918, Railton supported the soldiers in their worst moments; he buried the fallen, comforted the wounded, wrote to the families of the missing and killed, and helped the survivors to remember and mark the loss of their comrades so that they were able to carry on. He was with his men at many battles, including High Wood, the Aisne, Passchendaele; he received the Military Cross for rescuing an officer and two men under heavy fire on the Somme. It was Railton's idea to bring home the body of an unidentified fallen comrade from the battlefields to be buried in Westminster Abbey, and on Armistice Day 1920, he was there in the Abbey as the Unknown Warrior was laid to rest with full honors. Although suffering from Post-Traumatic Stress Disorder, he returned to work as a parish priest in Margate, where he took particular interest in supporting ex-servicemen who had returned home to the aftermath of a terrible war and crippling unemployment. While the story of the Tomb of the Unknown Warrior has been told before, this is the first book to explore David Railton's life and war, and of 'the padre's flag' he used as an altar cloth and shroud throughout the war. The flag was consecrated a year after the burial of the Unknown Warrior and hangs in Westminster Abbey to this day."--Publisher's description
Keywords: Railton, David -- 1884-1955; Railton, David / 1884-1955; Military chaplains / Church of England / Biography; Military chaplains / Great Britain / Biography; Soldiers' monuments / England / London; Sepulchral monuments / England / London; World War, 1914-1918 / Unknown military personnel; Biografie